Analysis of The Level of Interest and Customer Satisfaction with The Implementation of Food Safety at Brownies Cinta Shop - Mellenia Putri Fiorentina; Achmad Ridwan Ariyantoro (Jurnal Teknologi Hasil Pertanian, 2024)
This study aimed to determine the level of interest and consumer satisfaction with implementing food safety in Brownies Cinta Mojosongo Urban  Village, Surakarta. This quantitative descriptive study uses a sample of 100 Brownies Cinta customers who have visited Brownies Cinta twice. Data collection uses the survey method, and data analysis uses two analytical techniques: the CSI (Customer Satisfaction Index) method and the IPA (Importance Performance Analysis) method. The results showed that the order of importance of food safety indicators from the most important were buildings and facilities, production equipment, storage, production location/environment, process control, employee health and hygiene, water supply, hygiene facilities (hand washing), employee training, facilities hygiene (COVID protocol). The analysis results on the CSI method obtained a value of 84.54%, which means that consumers are satisfied with the food safety implementation carried out by Brownies Cinta Mojosongo. The analysis using the IPA method shows that the food safety indicator that needs to be improved is the production location/environment.